Compota based on sweet potato (Ipomoea batatas) adding pineapple (Ananas comosus) and banana (Musa x paradisiaca): organoleptic, physicochemical and microbiological characteristics (Agroindustrial Science, 2021)
The objective of this study was to make a compote based on sweet potato (Ipomoea batatas) adding pineapple (Ananas comosus) and banana (Musa x paradisiaca) to improve its organoleptic characteristics, which meet the established parameters pH, ° Brix, acidity and humidity and at the same time analyze the acceptance of the product through sensory evaluation. For the elaboration, a unifactorial model completely randomized design was used, the study factor acted with three levels for which the experimentation required 5 treatments with three 3 repetitions each. The best treatment was identified through a sensory analysis with 10 panelists in which the characteristics of flavor, consistency and degree of acceptance were evaluated. The results obtained identified the treatment purple sweet potato 44% + pina 20% + banana 36% and white sweet potato 44% + pina 20% + banana 36% as the best.
Keywords: compote; sensory evaluation; sweet potato; microbiology; physicochemical analysis